Justicia weihongjinii, a new species of Acanthaceae from Guangxi, China - Tong, Yi; Huang, Yusong; Deng, Yunfei (Phytotaxa, 2016)
A new species of Justicia (Acanthaceae), J. weihongjinii, is described and illustrated from Guangxi, China. The species belongs to sect. Harnieria and is similar to J. kwangsiensis and J. kouytchensis, but differs by the characters of lower lip of corolla pink, inflorescence bracts leaf-like and margin conspicuously undulate, calyx glabrous with conspicuous membranous margin and capsule longer than the calyx. The new species is endemic to Guangxi and grows on the limestone hills. The conservation status of the new species is assessed as “Data Deficient” (DD) according to IUCN Red List Category and Criteria.